2015
DOI: 10.1097/won.0000000000000126
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Specialty Practice Nursing Care on Health-Related Quality of Life in Persons With Ostomies

Abstract: Patients who received specialized ostomy care experienced significant improvements in HRQOL compared to patients who were not cared for by specialist nurses. Our findings strongly suggest that patients undergoing ostomy surgery should be provided access to a nurse specialist in ostomy care since our results highlight the potential benefit promoting the HRQOL of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 12 publications
1
29
0
1
Order By: Relevance
“…Our findings also match other studies that reported a more positive adjustment to a stoma after hospital discharge when patients received care from a nurse specialized in ostomies [12,13]. However, our study included a longer evaluation period for results than some of the mentioned studies (which only evaluated three months).…”
Section: Contributions In Terms Of Valuesupporting
confidence: 89%
See 1 more Smart Citation
“…Our findings also match other studies that reported a more positive adjustment to a stoma after hospital discharge when patients received care from a nurse specialized in ostomies [12,13]. However, our study included a longer evaluation period for results than some of the mentioned studies (which only evaluated three months).…”
Section: Contributions In Terms Of Valuesupporting
confidence: 89%
“…The role of stoma care nurses, annual follow-ups, and initial and long-term education has developed, and is essential to prevent poor use of the devices and accessories. This can lead to reduced prescription costs, have a positive effect on patients' health-related quality of life (HRQL), and reduce issues associated with adverse events, healthcare resources, and healthcare costs [10][11][12][13]. Although there are several studies on the improvement in quality of life of ostomy patients, such as those cited above, none of them evaluate a new model of comprehensive patient management such as the one that has been implemented in our region.…”
Section: Introductionmentioning
confidence: 99%
“…An ostomy was programmed for 81.1% and an emergency for 18.9%. Programmed procedures were more common in Group I, whilst emergencies were more common in Group II [25]. Regarding the type of ostomy, 51.6% was colostomy, 28.7% ileostomy, and 16.5% urostomy.…”
Section: Methodsmentioning
confidence: 99%
“…The case study is based on the implementation in hospitals of education programs for nurses, specializing them in the provision of care to recently ostomized patients; i.e., specialist in ostomy care (SOC) nurses. Coca et al [25] followed an observational study approach in general hospitals in Spain to show how stoma patients with access to SOC nurses experienced significant improvements compared to patients without access to specialist nurses. Here, the same approach evaluates whether this program is cost-effective and results in economic savings for the health system, comparing the evolution of recently ostomized patients at hospitals with and without SOC nurses, taking into account the adverse events patients had to face and their health expenditures.…”
Section: Introductionmentioning
confidence: 99%
“…The preparation and implementation of these protocols involves the use of high quality scientific evidence, as well as the use of pointers to evaluate them, which involve the complete diagnostic of the colorectal neoplasia, determination of the carcinoembryonic antigen (CEA) serum in the post-operative period, lymph nodes exams, daily cleanse of the operative wound, reference to the oncologist, use of chemotherapy adjuvants after 8 weeks of the surgery and evaluation of the obstruction from the colonoscopy. Beyond that, the evaluation of the hospital costs forms a factor to determine the patient satisfaction [42] [43].…”
Section: Jessica T Defrank 2007mentioning
confidence: 99%